Electric Power Supply System Of An Overhead Crane And Its Impact On Leaching Safety At The Cajamarquilla Zinc Refinery - GARCIA GONZALES, JAVIER SATURNINO; CACHO CHAVEZ, ENA MIRELLA (LACCEI, 2025)
Abstract– The objective of this project is to implement the electrical system of the primary power source of the overhead crane, located in the leaching area of ​​the Cajamarquilla refinery, to improve the availability and safety in the use of the overhead crane. To do this, it began with the collection of information on the current condition of the overhead crane. It was identified that the recurring failure occurred in the electrical power supply system. To determine the areas susceptible to improvement, an evaluation of the current state of the equipment was carried out, and then planning was carried out and what type of system could replace the existing one was evaluated, since the current system is deficient, causing the equipment to become inoperative, delaying the scheduled work with the crane. At the same time, the current condition of the equipment does not guarantee safe working conditions, exposing the collaborators who use the equipment. Of the different electrical systems that are found for overhead cranes, 2 systems were identified that could replace the existing one: the C-Track System and the Extensible System. Finally, the 2 systems were economically evaluated in terms of cost and installation times. Keywords– Festoon system; cable trolleys; electrical system, Extendable System, C-Track System.